Heavy-duty trucks. - Milton, Joyce; Courtney, Richard ill. (NY : Random House, 2000)
Describes different kinds of trucks, including tractor- trailers, auto haulers, garbage trucks, bulldozers, dump trucks, and cranes.
470
Accelerated Reader AR
Keywords: Trucks -- Juvenile literature